Nicotine Addiction Treatment Summary - Hofman, Michał; Janecka, Julia; Nadolny, Filip; Śniatała, Alicja; Jabłoński, Jędrzej; Dudek, Adam; Kania, Martyna; Adamowska, Agnieszka; Bartkowiak, Hanna; Damian Grubski, (Journal of Education, Health and Sport, 2025)
Nicotine addiction is a leading cause of preventable illness and death worldwide. This review summarizes current treatment options, focusing on both behavioral and pharmacological methods used in Poland and internationally. Effective strategies include nicotine replacement therapy (NRT), medications like cytisine, varenicline, and bupropion, as well as structured psychotherapy. Combining medical and psychological approaches significantly improves cessation outcomes and reduces the global burden of tobacco use. Introduction Tobacco use remains a major global health issue, contributing to millions of deaths annually. Nicotine’s addictive properties make quitting challenging despite widespread awareness of its risks. Effective treatment requires a comprehensive approach, combining behavioral support and pharmacotherapy. This paper reviews current methods of nicotine addiction treatment, with an emphasis on practices in Poland and globally. Aim of the Study This study aims to present a clear overview of evidence-based nicotine addiction treatments, with a focus on therapies available in Poland. It evaluates the effectiveness of both behavioral and pharmacological interventions to support healthcare professionals in smoking cessation efforts. Materials and Methods A literature review was conducted using PubMed and Google Scholar. The study includes international and Polish guidelines, scientific articles, and clinical data related to nicotine addiction therapy. Sources span behavioral interventions, NRT, and pharmacological treatments like cytisine, varenicline, and bupropion. Conclusion Nicotine dependence is treatable through a combination of behavioral and pharmacological methods. In Poland, comprehensive treatment programs and modern pharmacotherapy are available and effective. Increasing access to these resources is essential to reducing smoking rates and improving public health.